2014
DOI: 10.2217/rme.14.33
|View full text |Cite
|
Sign up to set email alerts
|

First Transplantation of Isolated Murine Follicles in Alginate

Abstract: Our results suggest that an artificial ovary is now conceivable, opening new perspectives to restore fertility in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…A number of variant polymers, classified as natural and synthetic polymers, have been reported for the construction of artificial ovaries [2]. Here, alginate acid sodium salt, as a type of hydrogel, was selected for the modeling of the proposed artificial oocyte due to its versatility, and also the fact that it has been reported as a suitable material for transplantable artificial ovary matrix [15], [16].…”
Section: Model Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of variant polymers, classified as natural and synthetic polymers, have been reported for the construction of artificial ovaries [2]. Here, alginate acid sodium salt, as a type of hydrogel, was selected for the modeling of the proposed artificial oocyte due to its versatility, and also the fact that it has been reported as a suitable material for transplantable artificial ovary matrix [15], [16].…”
Section: Model Presentationmentioning
confidence: 99%
“…It is biocompatible and shows non antigenicity [4]. Alginate was also proposed as a candidate material for transplantable artificial ovary matrices in 2012 [3], [5]. It has also been reported that different combinations with alginate such as matrigel could be successfully employed for transplanting murine ovarian cells [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After this period of transplantation, they observed survival and proliferation of ovarian cells and formation of capillaries inside the remaining alginate-matrigel matrix. However, since matrigel cannot be used in a clinical setting, Vanacker et al [19] replaced their alginate-matrigel matrix with a good manufacturing practice (GMP)-produced alginate (NovaMatrix 1 % SLM). They repeated the same experimental design, but also added isolated murine preantral follicles and grafted the matrix inside a peritoneal pocket (Fig.…”
Section: Alginatementioning
confidence: 99%